Characterization of marine debris at Bluka Teubai Beach, North Aceh, Indonesia: Composition, density, and temporal patterns - Imamshadiqin, Imamshadiqin; Andika, Yudho; Syahputra, Andika; Erniati, Erniati; Salmarika, Salmarika (Universitas Malikussaleh, 2025)
Marine debris consists of materials discarded or unintentionally introduced into the marine environment by human activities. The increasing volume of marine debris is largely attributed to human activity near coastal areas. Bluka Teubai Beach, North Aceh, a popular visitor destination, has a high potential for waste accumulation. This study, conducted in May 2024, employed a purposive sampling method to assess marine debris. The research area was divided into three stations with distinct characteristics, using the line transect method. Results from Bluka Teubai Beach identified two primary waste categories: organic and inorganic. Organic waste included wood, bamboo, and coconut husk, while inorganic waste consisted of plastic, glass, metal, and rubber. Among organic waste, wood exhibited the highest absolute density (0.456 items/m²) and relative density (53.950%), followed by bamboo (0.317 items/m², 39.641%) and coconut husk (0.049 items/m², 6.409%). The overall density of organic waste at Bluka Teubai Beach was highest for wood (0.23 items/m²), with an average relative density of 58.640%. For inorganic waste, plastic had the highest absolute density in pieces (2.24 items/m²) and relative density in pieces (96.968%). The highest absolute density and relative mass of inorganic waste were also found in plastic (99.94 g/m² and 64.36%, respectively). Temporal analysis revealed that organic waste accumulation peaked on Fridays, while inorganic waste was most abundant on Tuesdays in terms of count and on Sundays in terms of mass. The results underscore the urgent need for targeted waste management strategies and continuous monitoring to mitigate marine debris pollution and protect the coastal ecosystem of Bluka Teubai Beach.